Deep cuts eaudiobook A novel. - Brickley, Holly (Books on Tape, 2025)
NATIONAL BESTSELLER • “Tender as a ballad and pleasurable as a pop song, Deep Cuts is both a romp into the indie sleaze era of the early aughts and a timeless love story.”—Coco Mellors, New York Times bestselling author of Blue Sisters “Warm, nostalgic, totally engrossing. I loved this novel.”—Liz Moore, New York Times bestselling author of The God of the Woods Look, the song whispered to me, that day in my living room. Life can be so big. It’s a Friday night in a campus bar in Berkeley, fall of 2000, and Percy Marks is pontificating about music again. Hall and Oates is on the jukebox, and Percy—who has no talent for music, just lots of opinions about it—can’t stop herself from overanalyzing the song, indulging what she knows to be her most annoying habit. But something is different tonight. The guy beside her at the bar, fellow student Joe Morrow, is a songwriter. And he could listen to Percy talk all night. Joe asks Percy for feedback on one of his songs—and the results kick off a partnership that will span years, ignite new passions in them both, and crush their egos again and again. Is their collaboration worth its cost? Or is it holding Percy back from finding her own voice? Moving from Brooklyn bars to San Francisco dance floors, Deep Cuts examines the nature of talent, obsession, belonging, and above all, our need to be heard.